1988
DOI: 10.1115/1.3243573
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of the Laminarization Phenomena in an Axially Rotating Pipe Flow

Abstract: Numerical predictions are compared with the experiments of swirling turbulent flows in a pipe where the swirl is driven by the pipe wall rotating around the pipe axis. The laminarization phenomena, that is, the deformation of the axial velocity profile into a shape similar to the laminar one and the decrease of the friction factor, caused by the pipe rotation can be predicted by the calculations applying the stress equation turbulence model. However, calculations applying two types of the k-ε two-equation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…The mean circumferential velocity has a parabolic profile shape and appears to be proportional to (r/R) 2 , independent of the Reynolds number and the rotation rates as shown experimentally [3][4][5]8] and numerically [10,13,14]. However, it is far from fully understood why such a universal velocity distribution exists.…”
Section: Discussionmentioning
confidence: 99%
“…The mean circumferential velocity has a parabolic profile shape and appears to be proportional to (r/R) 2 , independent of the Reynolds number and the rotation rates as shown experimentally [3][4][5]8] and numerically [10,13,14]. However, it is far from fully understood why such a universal velocity distribution exists.…”
Section: Discussionmentioning
confidence: 99%
“…However only limited results were presented so it is difficult to conclude the true performance of eddy-viscosity models. The conclusions of Torri et al are however in contrast with the work of Hirai et al 14 and Wallin et al 15 who concluded that the k − ε fails (with or without the Richardson correction for Hirai et al). Speziale et al 12 (also discussed in Jakirlic et al 8 ) demonstrated the theoretical inability of standard two-equation models to account for rotation, however this appeared to be for a flow subject to a rotating reference frame and the additional complexity of the fully-developed inlet flow means that in practice the performance of these models may partly reproduce the rotation-effects because of the influence of the changing pressure and azimuthal velocity 8 .…”
Section: Rotating Pipementioning
confidence: 76%
“…This was confirmed by the Reich and Beer [15] as well. Laminarization of the velocity profiles was discovered by several other authors such as Murakami and Kikuyama [12], Hirai et al [9] and Imao et al [10], who studied the flow in axially rotating pipes. The most important characteristic of the laminarization phenomenon is its axial velocity profile; the turbulent flow profile becomes similar to the laminar velocity profile due to the pipe rotation.…”
mentioning
confidence: 92%